Gender Group Differences in STEAM Learning: How Balloon-Powered Car Enhance Science Process Skills and Creative Thinking Skills in Elementary Students? - Devi Ayu Nur'aini; Annisa Ulfa Yana; Rahmat Firman Septiyato; Baoyu Li (Postgraduate, University of Mataram, 2026)
This study aims to determine the science process skills (SPS) and creative thinking skills (CTS) of elementary school students during STEAM based balloon-powered car project. A quasi-experimental with 29 sixth-grade students assigned to three group types: all-boys, all-girls, and mixed-gender. Students participated in a four-session STEAM learninng sequence, and their SPS and CTS were assessed through rubric-based observations and interviews. Kruskal-Wallis analysis showed no statistically differences among three groups for either SPS (H = 2.061, p = 0.357) or CTS (H = 3.157, p = 0.206), with very small effect sizes. Although minor descriptive tendencies appeared, in SPS, the boys group showed slightly higher performance in the classifying and prediction indicators, while the girls group excelled in the communication indicator. In CTS, the girls group excelled in the fluency, flexibility, and elaboration indicators, while the boys group excelled in the originality indicator. Overall, all groups achieved moderately high SPS and CTS scores, indicating that the STEAM project effectively facilitated scientific inquiry and creative thinking irrespective of gender composition. These findings confirm that well-designed STEAM-based projects can provide equal opportunities for all students to develop their SPS dan CTS simultaneously.